2004
DOI: 10.1128/jb.186.10.3086-3096.2004
|View full text |Cite
|
Sign up to set email alerts
|

Instability of Pathogenicity Islands in Uropathogenic Escherichia coli 536

Abstract: The uropathogenic Escherichia coli strain 536 carries at least five genetic elements on its chromosome that meet all criteria characteristic of pathogenicity islands (PAIs). One main feature of these distinct DNA regions is their instability. We applied the so-called island-probing approach and individually labeled all five PAIs of E. coli 536 with the counterselectable marker sacB to evaluate the frequency of PAI-negative colonies under the influence of different environmental conditions. Furthermore, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
112
5
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(123 citation statements)
references
References 45 publications
3
112
5
1
Order By: Relevance
“…Dobrindt et al reported that PAI III536 was more common than PAI II536 or PAI I536 in UPEC strains, including isolates from women with chronic UTIs, in contrast with our UPEC isolates from patients without catheters [11]. In other reports [20], PAI III536 and PAI II536 were reported as unstable PAIs, which could be the reason for the difference between our results and Sabate et al's findings. PAI IJ96, and PAI IIJ96 were not identified in our UPEC isolates.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Dobrindt et al reported that PAI III536 was more common than PAI II536 or PAI I536 in UPEC strains, including isolates from women with chronic UTIs, in contrast with our UPEC isolates from patients without catheters [11]. In other reports [20], PAI III536 and PAI II536 were reported as unstable PAIs, which could be the reason for the difference between our results and Sabate et al's findings. PAI IJ96, and PAI IIJ96 were not identified in our UPEC isolates.…”
Section: Discussioncontrasting
confidence: 56%
“…Our results also showed that one UPEC isolate from patients with an implanted catheter and four UPEC isolates from patients without urinary catheters suffering from sepsis carried only PAI IV536 as a single PAI marker. The high frequency of PAI IV536 has been documented in commensal isolates, although some studies have shown that HPI participates in pathogenicity of extraintestinal pathogenic E. coli [14,20]. The high frequency of PAI IV536 shows this Table 3.…”
Section: Discussionmentioning
confidence: 94%
“…These results may be explained by the fact that, although associated to higher potential to form biofilm, 4,45 haemolysin is a trait involved in invasiveness and could be secreted in the planktonic lifestyle in order to injure host tissue and then colonize it by forming the biofilm. Unexpectedly, even when fimB was found in the genetic pool of the 3 isolates, fimA gene was not detected as the other virulence factors; this may be due to the loss of genes or pathogenicity islands in UPEC associated with different environmental conditions, according to Middendorf et al 46 Induction of siderophore related genes in BFC conditions indicate that UPEC may use a broad repertoire of systems to acquire iron in order to survive within the iron-limited urinary tract. 47 Interestingly, UPEC strains causative of asymptomatic bacteriuria, while lacking classical virulence factors such as fimbriae, express the full complement of iron acquisition systems, providing further evidence for the requirement of iron uptake during successful urinary tract colonization.…”
Section: Discussionmentioning
confidence: 99%
“…It has been generally assumed that bacteria pay a physiological price -fitness deficit-for their acquisition of resistance to antibiotics [11]. Some mechanisms compensating for these costs of quinolone resistance in E. coli have been found [3,12]. Our study showed that quinolone-resistant uropathogenic strains of E. coli exhibit significantly reduced adhesive potential but relatively high resistance to serum and macrophage bactericidity.…”
Section: Discussionmentioning
confidence: 47%